Aromatic Plant Trade and Livelihood Strategies in Rural Nepal: A Case of Wintergreen in Dolakha District - Subedi, Madhusudan (Occasional Papers in Sociology and Anthropology, 2010)
The objective of this paper is to assess opportunities for Wintergreen, a natural product's intervention on poverty reduction, strengthening local governance, and improving resource management. DOI: 10.3126/opsa.v11i0.3032 Occasional Papers in Sociology and Anthropology Vol.11 2009 84-103